Adamantane Substitution Effects on Crystallization and Electrooptical Properties of Epindolidione and Quinacridone Dyes. Issue 12 (24th September 2021) - Richtar, Jan; Ciganek, Martin; Prochazkova, Anna Jancik; Kovalenko, Alexander; Seelajaroen, Hathaichanok; Kratochvíl, Matouš; Weiter, Martin; Yumusak, Cigdem; Sariciftci, Niyazi Serdar; Lukeš, Vladimir; Krajcovic, Jozef
Abstract: The synthesis, experimental and theoretical study of the novel air‐stable four adamantane‐bearing dyes based on the trans‐ epindolidione (EPI ) and trans‐ quinacridone (QA ) cores are presented. Compared to the parent EPI and QA, the methyl‐/ethyladamantyl substitution ensures that their structural stability in crystals is preserved due to the self‐organizing properties of adamantyl groups. The investigated materials are solution‐processable in common organic solvents and possess excellent thermal stability. The very good solubility was achieved by a one‐step short and easy synthesis, which resulted in moderate yields of a new family of synthesized dyes. The ethyladamantyl EPI derivative (3 ) exhibits a unique rise in thermal stability reaching 412 °C. The resulting electrochemical band gap carried out on thin‐film evaporated on ITO‐coated glass electrodes was in the range of 2.4–2.5 eV. The experimental HOMO energies range from −6.2 to −6.0 eV, and LUMO energies lay between −3.7 and −3.5 eV. The prepared compounds are characterized by strong fluorescence in solutions and in powder, suggesting a decrease in the extent of non‐radiative relaxation processes. Abstract : Bulky adamantyl groups strongly impacted thermal stability, molecular packing, fluorescence efficiency and significantly improved solubility and processability of otherwise nearly insoluble hydrogen‐bonded pigments quinacridone and epindolidione. A robust synthetic strategy involved one‐step nucleophilic substitution which provided four target alkylated dyes. Efficient self‐organizing properties of adamantyl groups resulted in distinct and highly ordered molecular packing.